Best Answer

assuming x*2-3x+2:

factors of -3:

-1,3 --> sum: 2

1,-3 --> sum: -2

(x-1)(x+3)

Q: How do you factorise- x2-3x 2 equals?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2a2b2+3a2b2-5abc

44

(x-5)(x+11)

15t+25 = 5(3t+5)

25x + 75 = 25*(x + 3)

Related questions

2a2b2+3a2b2-5abc

44

To factorise is to find the numbers that divide into the original number by only using prime numbers. For example factorise 20 = 2 times 2 times 5

(x-5)(x+11)

15t+25 = 5(3t+5)

-9(a + b)

25x + 75 = 25*(x + 3)

x(2+3)-70 5x-70 70/5= x-14

2(3n+4)

we factorise a number by finding the common factor. example: 2x+6 = 2 is the common factor the 2 is then put outside the bracket 2x+6 = 2(x+3)

4c(-sq+2)

3 x (m - 2)